WASTE LOGISTICS AND FEA MANAGEMENT: ADAPTATION OF COMMUNITIES TO THE EUROPEAN GREEN DEAL - Shvets, Fedir; Vasyliv, Volodymyr (Current Problems of Sustainable Development, 2026)
The article substantiates the theoretical and practical principles of municipal solid waste logistics modernization and develops comprehensive recommendations for the foreign economic activity management of Ukrainian territorial communities under the imperative of adapting to the European Green Deal and circular economy standards. The study addresses a profound contradiction between Ukraine’s European integration environmental commitments and the archaic state of communal infrastructure at the local government level. Methodologically, the research integrates statistical analysis of MSW indicators with mathematical and stochastic modeling of transport flows. The authors analyze the destructive factors of the current system, including a landfilling rate exceeding 90%, 30% obsolescence of the specialized fleet, and 40% efficiency losses due to empty routing runs. To bridge this digital and technological gap, an innovative approach to municipal reverse logistics based on the Internet of Things architecture is proposed. It is proven that replacing static routing with dynamic stochastic models – triggered when container fill levels reach 80–85% – generates a substantial optimization effect. This transition cuts community fuel and logistics operational costs by 25–30%, reduces the municipal carbon footprint by 30%, and increases secondary raw material utilization 4 to 5 times due to digital product traceability. Given the high capital intensity of such innovations as a primary barrier, the study emphasizes the critical role of intensifying municipal foreign economic activity management. A matrix of international financial and investment instruments is developed, focusing on diversifying funding sources through EU grants, the Ukraine Facility, targeted green loans, and cross-border public-private partnerships. Ultimately, the paper provides a step-by-step algorithm for local authorities, including IoT deployment, GIS integration, institutional strengthening through local Eurointegration offices, and transitioning to the European “pay-as- you-throw” tariff policy. The practical implementation of these measures turns environmental challenges into municipal capitalization, securing long-term community viability.